Early evaluation in Hevea: Growth and yield at the juvenile phase - Varghese Y A; John A; Panikkar A O N; Premakumari D; Sethuraj M R (Indian Journal of Natural Rubber Research, 1993)
Thirteen clones, with yield levels ranging from high to low, were evaluated for juvenile growth, yield and yield components at the nursery stage to identify early selection parameters. Computation of growth and performance indices revealed that, in general, high yielders recorded higher values in comparison to medium and low yielders. Correlations of juvenile yield with the yield components, plugging index, DRC and panel length at the age of three years were highly significant and 54.5 per cent of the total variability for juvenile yield could be accounted for by these three variables. Correlations for girth and juvenile yield between two and four years of age were also highly significant. The results reveal that based on girth and yield at two years, high yielders could be selected. However, certain vigorous medium yielders are also likely to record high juvenile yield. A rational approach to reduce progeny size as well as to ensure evaluation of all potential high yielders would be to select all genotypes giving better performance index than the general mean.
Keywords: Early evaluation; Early evaluation; Growth index; Growth index; Hevea brasiliensis; Hevea brasiliensis; India; India; Performance index; Performance index; Plant breeding; Plant breeding; Yield components; Yield components